Probabilistic seismic hazard assessment for the South Central Vietnam - Phuong, Nguyen Hong; Truyen, Pham The (Vietnam Journal of Earth Sciences, 2015)
In this paper, the probabilistic seismic hazard maps for the South Central Vietnam are presented. An earthquakes catalog updated until 2014 and most recent seismotectonic and geodynamic information were used for delineation of 14seismic source zones in the study area. The Toro et al. (1997) attenuation equation was used for the PSHA. The hazard maps show distribution of the mean peak ground acceleration (PGA) with a 10%, 5%, 2% and 0.5% probability of exceedance in 50 years. The highest values of PGA are observed in the continental shelf of the South Central Vietnam, in the 1090 meridian source zone, where the maximum PGA values are 0.12, 0.15, 0.2 and 0.28 g corresponding to the return times of about 500, 1000, 2500 and 10 000 years, respectively. In addition, two seismic source zones that can produce strong ground shaking off-shore South Central coast are Cuu Long -Con Son and Thuan Hai -Minh Hai. For the time period of about 1000 years, the highest shaking intensity within these source zones reaches the value of VIII (I=VIII by MSK-64 scale).In the territory of South Central Vietnam, the strongest shaking are observed in the Quang Nam and Quang Ngai provinces, in the Hung Nhuong -Ta Vi seismic source zone. For the return times of about 500, 1000, 2500 and 10 000 years, the highest PGA values in this zone are  0.1, 0.12, 0.14 và 0.17 g, respectively.Strong ground shakings are also observed in some other seismic source zones as Tuy Hoa -Cu Chi, Hau river and Nha Trang -Tanh Linh.ThePGA maps present both short-term and long-term forecasts of seismic hazard in the South Central Vietnam and can be used as a reference for antiseismic design and many engineering applications.References Cornell, C. A., 1968: Engineering Seismic Risk Analysis, Bull. Seim. Soc. Am.,58, pp. 1583 - 1606. Department of Science and Technology of the Ho Chi Minh City, People Committee of Ho Chi Minh city, 2008: 1 Report of the 1st Stage of implementation of the Project “Seismic Microzoning of the Ho Chi Minh city”, Ho Chi Minh City (in Vietnamese). International Atomic Energy Agency, 2003: Site Evaluation for Nuclear Installations. IAEA Safety Standards Series No. NS-R-3, IAEA, Vienna. Institute of Energy, EVN, Ministry of Industry and Trade, 2003: Feasibility report of investment and construction of NPP in Ninh Thuan, Vol. 3, Appendix, Book 2/2 (in Vietnamese). Keilis-Borok, V.I., Knopoff, L., Rotwain, I.M., 1980: Burst of aftershocks, long-term precursors of strong earthquakes, Nature, Vol. 283, 259-263. L. T. Son et al., 2006: Investigation of the Phan Thiet - Vung Tau earthquake of November 8, 2005. Field trip report, Dept. of earthquake observation, Institute of Geophysics, Hanoi. McGuire, R.K., 1976: FORTRAN computer program for seismic risk analysis, U.S. Geol. Survey Open - File Rept. 76-67, 89. N. K. Mao, 1974: Seismic zoning of South Vietnam. Bulletins of Universities. N. L. Minh et al, 2012: The first peak ground motion attenuation relationships for North of Vietnam, Journal of Asian Earth Sciences, doi: 10.1016/j.jseaes.2011.09.012. N. H. Phuong, 1991: Probabilistic Assessment of  Earthquake Hazard in Vietnam based on Seismotectonic Regionalization, Tectonophysics, 198, 81-93, Elsevier Publisher. N. H. Phuong, 1993: Probabilistic earthquake hazard assessment for the territory of Vietnam, Ph.D. thesis, Smith Institute of Physics of the Earth, Academy of Sciences of Russian Federation, Moscow (In Russian). N. H. Phuong, 1999: Investigation of the Relation between Seismicity and Elements of Geodynamics along the Southeastern Coast of Vietnam. Proceedings of the International Workshop on Tectonics, Geodynamics and Natural Hazards in West Pacific-Asia. Journal of Geology, Series B, No13-14/99, pp.179-193. N. H. Phuong, 2004: Probabilistic seismic hazard maps of Vietnam and the East Vietnam Sea. Vietnam Journal of Earth Sciences, 26(2), 97-111 (in Vietnamese). N. H. Phuong, 2010: Chapter V. Seismic hazard and seismic risk in the coastal zones and islands of Vietnam. In: B. C. Que (editor). “Earthquakes and tsunamis hazards in the coastal zones of Vietnam”, Natural Science and Technology Publ. House, Hanoi, 312 pp. (in Vietnamese). N. H. Phuong, B. C. Que, N. D. Xuyen, 2012: Investigation of tsunami sources, capable of affecting the Vietnamese coast. Natural Hazards, 64(1) pp 311-327. DOI: 10.1007/s11069-012-0240-3, October 2012. N. H. Phuong et al., 2014: Assessment of earthquake and tsunami hazards in the Ninh Thuan province for site approval of the NPPs. Final report of the National Scientific Research Project No 02-2012/HĐ-ĐTĐL, Hanoi. N. D. Xuyen et al., 1981: Additional earthquakes data from questionnaires. Field trip report on earthquakes during 1979 - 1981. Department of Physics of the Earth - Vietnam Institute of Sciences, Hanoi (in Vietnamese). N. D. Xuyen et al., 2004: Final report of the National scientific research project on “Study of earthquake prediction and ground motion in Vietnam. Final report of the National scientific research project on “Study of earthquake prediction and ground motion in Vietnam”, Institute of Geophysics, Hanoi, (in Vietnamese). Ordaz M., Aguilar A., Arboleda J. CRISISS99. University of Mexico (UNAM). Petersen, M. D. Dewey, J., Hartzell, S., Mueller, C., Harmsen, S., Frankel, A.D., Rukstales K., 2004: Probabilistic seismic hazard analysis for Sumatra, Indonesia and across the Southern Malaysian Peninsula. Tectonophysics,390 (2004) 141-158. T. V. Hung and Kiyomiya, O., 2012: Ground motion attenuation relationship for shallow strike-slip earthquakes in northern Vietnam based on strong motion records from Japan, Vietnam and adjacent regions, Structural Eng./Earthquake Eng., JSCE, 29: 23-39. P. V. Thuc, 2008: Relationship of earthquakes and volcanoes activities in the South Central Coast, Journal of Marine Science and Technology, No 2(8), Hanoi. Toro, G. R., Abrahamson, N. A. and Schneider, J. F., 1997: Engineering Model of Strong Ground Motions from Earthquakes in the Central and Eastern United States, Seismological Research Letters, January/February. V. M. Giang, 2000: Earthquakes and other natural disasters through the historical data.  Institute report, Institute of Geophysics.